Finishing properties of corner rack from Kelempayan (Neolamarckia cadamba) / Nor Izati Ismail - Ismail, Nor Izati (2014)
The study focus on finishing system applied on the furniture. The main objectives of this study are to determine the finishing properties of Kelempayan (Neolamarckia cadamba) by using different finishing system and to study furniture design of corner rack from Kelempayan wood (Neolamarckia cadamba). The finishing system used are system A (sanding + sealer + top coat) and system B (sanding + top coat). Surface roughness test, tape adhesion test, household test and pencil hardness test was performed in order to determine which system are the best to be applied. As a result, system A was found to be the better system to be applied on the furniture since all the testing results shows than system A was better than system B.